2022
DOI: 10.1097/gox.0000000000004061
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating Excellence in Plastic Surgery Residency

Abstract: Background: Residents can achieve distinction by discerning which areas of achievement are worth additional focus at each stage in training. Our survey examines the perspectives of faculty members affiliated with Accreditation Council for Graduation Medical Education-accredited plastic surgery residency programs regarding qualities indicative of resident excellence. Methods: A survey including Likert scales and rank-ordering was distributed to plastic surgery program directors and faculty with the intent to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Furthermore, when program leaders were asked what features made a particular resident excellent, they described traits such as personality, leadership, and case preparation—little mention was made of research productivity. 20…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, when program leaders were asked what features made a particular resident excellent, they described traits such as personality, leadership, and case preparation—little mention was made of research productivity. 20…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when program leaders were asked what features made a particular resident excellent, they described traits such as personality, leadership, and case preparation-little mention was made of research productivity. 20 There are an increasing number of publications as physicians progress in their individual training-on average, two publications by general surgery residency graduation (for those who attended) and six publications by plastic surgery residency graduation. Figures 2-4 illustrate the faculty publication count at each of the three graduation milestones.…”
Section: Discussionmentioning
confidence: 99%
“…When defining an excellent resident at the early years, faculty often deem traits such as bedside manner and personality as the most important, whereas in later years, technical proficiency and leadership capability are more sought after. 11 We present here a list of traits that define an excellent plastic surgeon, including both “hard” and “soft” skills such as technical soundness and compassion. These hard skills such as technical soundness, although important in the practicing plastic surgeon, can typically be improved with practice and repetition.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Furthermore, a recent survey of faculty engaged in resident education found that research productivity was one of the least important metrics when considering what defines an excellent resident; rather, traits such as leadership capability, operative expertise, bedside manner, and personality were of most importance. 11 This raises question as to what aspects should be sought after during residency selection, and whether the way we currently select residents is adequately assessing these characteristics.…”
Section: The Current Paradigm Of Resident Selectionmentioning
confidence: 99%
See 1 more Smart Citation